Comorbidities in Psoriasis: A Narrative Literature Review - N, Nursyarifah; Nopriyati N; Thaha A; Diba S; Kartowigno S; Kurniawati Y (RSUP Dr Moh Hoesin Palembang, 2023)
Comorbidities in Psoriasis: A Narrative Literature Review. Psoriasis is a chronic inflammatory disease with multisystemic morbidities. The most common comorbidities of psoriasis include psoriatic arthritis, cardiovascular disease, metabolic syndrome, overweight/obesity, inflammatory bowel disease, and mental disturbance in terms of depression. Evidence shows an association of psoriasis with comorbid diseases and have been proposed as related to the chronic inflammatory status of psoriasis. The presence of such comorbidities affects the therapeutic choices for clinicians in comprehensive way. The understanding of these pathogenesis relation and regular screening for early diagnosis of the comorbid diseases will certainly lead to better management of the disease. This is because the management paradigm of psoriasis does not only target repair of skin lesions but also works together with other scientific disciplines to prevent and treat comorbid diseases holistically. Patient often visit the clinician regularly and it is important to recognize and address early signs of psoriatic comorbidities to prevent further deterioration and improve quality of life. The purpose of this review is to summarized pathogenesis and screening recommendation of comorbidity associated with psoriasis, which may be essential for future clinician guideline in order to achieve holistic therapy of psoriasis and quality of life improvement.